Numerical Modeling of an Umbrella-Shaped Bolt and Its Anchorage Characteristics in Rock Engineering - Xiong, Yong; Chen, Hang; Cheng, Yonghui; Hu, Shenggang; Wang, Zhaofeng; Gao, Yaohui (Frontiers in Earth Science, 2022)
The umbrella-shape bolt (U-bolt) is a novel type of mechanical bolt used for rock reinforcement . It is made of a smooth steel bar, hinges, rigid rods, sliding blocks and hinges. During installation and operation, the tension of the bolt is converted into the extrusion force on the rock mass deep in slope, so that, the higher compressive strength of the rock mass is used to obtain the greater friction force and anchoring force. This paper provides the structural and mechanical analysis of the U-bolt, and the relation between penetration and point normal stress is discussed. Based on these analysis, a simulation method for U-bolt is proposed. The bolt elements are identified at first, then the penetration on the rockmass is calculated, and the tensile strength of bolt elements is increased to reasonable value. Meanwhile, the method is applied to a deep buried rock reinforcement and a rock slope, and simulation results reveal that the U-bolt can alleviate the fracturing degree and reduce the depth and displacement of the excavation damage zone (EDZ), as well as decrease the landslide distance.